Pelatihan Penggunaan Aplikasi Hiilsinergi dalam Meningkatkan Efisiensi dan Efektivitas Pengelolaan Organisasi di Era Digital - Dinata, Imam; Idham, Idham; Yusuf, Siti Agrippina Alodia; Rizkillah, Muhammad (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
Organization is one of the most important elements in the management function, which includes planning, organizing, actuating, and controlling. The Department of Manpower and Transmigration (Disnakertrans) of Central Lombok is a regional government agency responsible for labor and transmigration affairs in Central Lombok Regency, West Nusa Tenggara. Organizational management is essential for improving operational efficiency and effectiveness, as well as adapting the organization to environmental changes. In managing certification training institutions, a supporting application system is needed to digitize the documents required during certification implementation. The Hiilsinergi application is a digital platform designed by the Association of Indonesian Training Institutions (HILLSI) to support management, collaboration, and synergy among Training Institutions (LPK) throughout Indonesia. This community service activity aims to enhance the capability of certification training institutions, government, and trainees in digitizing the necessary documents within the Hiilsinergi application. The community service was conducted offline on March 4, 2025, and was attended by 30 participants consisting of representatives from certification training institutions, government bodies, and training participants. The results of the activity showed high interest and active engagement from certification training institutions, the government, and trainees in the discussions, and resulted in the creation of a Hiilsinergi application module document as a guideline for these stakeholders.